Acculturation Scale to Russia (ASR) for International Students: Development and Psychometric Verification - Alfredo Ardila; Olga V Maslova; Irina A Novikova; Dmitriy A Shlyakhta; Yussara Yussara Aguilar (Peoples' Friendship University of Russia (RUDN University), 2019)
The growing number of migrants makes it relevant to study the problem of acculturation to a new culture and to develop adequate methodological tools for assessing acculturation. Acculturation scales are a common tool for studying the adaptation of international citizens; in Russia, however, there is a shortage of them. The purpose of this study was to develop a short, easy to use, and not requiring translation into the mother tongue scale, aimed at determining the level of acculturation. When developing the methodology, we relied on the analysis of the available acculturation scales and on the recommendations proposed by van de Vijver et al. This study included the following stages: development of the initial version of the scale, testing and analysis of comprehensibility of the scale questions, psychometric analysis, repeated testing and psychometric veriﬁcation, and ﬁnally, determining external validity. At the various stages, the study covered 445 international students (42% female) from 71 countries. For psychometric analysis, descriptive statistics methods, Cronbach α and MacDonald ω coeﬃcients, bifactor analysis were used. To check the external validity, the method of expert evaluations (16 experts are teachers of the Russian language, basic disciplines, tutors on educational work) and correlation analyses were used. As a result, the proposed Acculturation Scale to Russia (ASR) has a high consistency (α = 0,89, ω = 0,91), three-factor structure (3 subscales were identiﬁed), and its satisfactory external validity. This scale can be used to assess the level of acculturation of international students in Russia.